DANSEIGO (BAHASA PRIA) DAN JOSEIGO (BAHASA WANITA) DALAM KOMIK “CHIBIMARUKOCHAN” - Nimas, Fransiska (Japanese Literature, 2013)
Nimas, Fransiska. “Danseigo and Joseigo in Chibimarukochan comics”. Thesis. Japanese Literature Department. Faculty of Humanities Diponegoro University. Pembimbing I. Lina Rosliana, SS, M.Hum. In this thesis the author researching on Danseigo and Joseigo in Chibimarukochan comics. Where Japan nowadays can be found through comics, anime, as well as magazines, where they use the language of Japan in the form of non-formal, used the male and female speakers of Japan therefore pleh. alas an author choosing this theme is because the author wanted to know how the use of language and mark men and women's language of Japan. In this study the author uses sumberdata from the original comics Japan Chibimarukochan 1 and 2 series. Where there are many languages in addition to the men and women‟s mark, as well as the language is easy to understand. Research on metede the author collects data from a variety of sources: primary sources from the comic Chibimarukochan 1 and 2 series . Secondary sources of documents, books, magazines, the internet etc. The use of the language of the men and women of Japan a non formal at commonly used to soften remarks or feminine showing in women. Whereas in males showed firmness and kemaskulinannya. Keywords: Danseigo and Joseigo pada komik Chibimarukochan .